2020
DOI: 10.5535/arm.2020.44.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Assessments for Sarcopenia in Patients With Stroke Who Can Walk Independently

Abstract: Objective To investigate variables for assessment of stroke-related sarcopenia that are alternative options to the current assessment for sarcopenia, which focuses on age-related sarcopenia and also has limitations in addressing sarcopenia due to weakness resulting from stroke. Methods Forty patients (17 men, 23 women; mean age, 66.9±15.4 years) with first-ever stroke who can walk independently were included. Muscle mass was determined by measuring ultrasonographic muscle thickness of vastus intermedius, rectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The EWGSOP suggests the gait speed test as an easy and valid method for assessing physical performance [ 3 , 15 , 16 ]. Gait speed has been performed to evaluate various health-related factors such as physical functions, health status [ 17 , 18 , 19 ], and quality of life [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EWGSOP suggests the gait speed test as an easy and valid method for assessing physical performance [ 3 , 15 , 16 ]. Gait speed has been performed to evaluate various health-related factors such as physical functions, health status [ 17 , 18 , 19 ], and quality of life [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study [48] compared ultrasound assessment of anterior and posterior aspects of the thigh with lean mass evaluated by DXA in middle-aged and older adults, showing a significant correlation. Moreover, a recent study suggested ultrasonographic muscle thickness of tibialis anterior as DXA alternative in evaluating muscle mass of stroke survivors [49].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation of other evaluating tools may be considered. In 2020, Jung et al [ 28 ] evaluated the effectiveness of ultrasound in measuring muscle thickness in the lower extremities along with other physical performance testing tools; it may be advantageous in the diagnosis and follow-up studies of sarcopenic patients.…”
Section: Discussionmentioning
confidence: 99%